Design and Implementation of a Negative Ion Generator Based on MQ-135 Sensor and Arduino Nano - Gunastuti, Dwi Anie; Lukas, Lukas; M. Lanny W. Panjaitan, M. (Emitor: Jurnal Teknik Elektro, 2025)
This paper presents an enhanced study on the design, modeling, and implementation of a Negative Ion Generator (NIG) based on the MQ-135 air-quality sensor and Arduino Nano microcontroller. The research combines theoretical modeling of corona discharge, electric field dynamics, and Cockcroft–Walton (C–W) voltage multiplication with experimental validation. Measured pollutant reductions ranged between 25–40% within 10 minutes of ionization, correlating well with theoretical predictions [1]. The proposed smart NIG offers low-cost, energy-efficient, and automated operation suitable for modern indoor environments, contributing to the development of intelligent IoT-based air-quality systems [2]